Antifungal Effect of Lavender Essential Oil (Lavandula angustifolia) and Clotrimazole on Candida albicans: An In Vitro Study. (13th October 2015) - Behmanesh, Fereshteh; Pasha, Hajar; Sefidgar, Ali Asghar; Taghizadeh, Mohsen; Moghadamnia, Ali Akbar; Adib Rad, Hajar; Shirkhani, Leyla
Abstract : Background . The treatment of candidiasis infections is an important problem in the health care system. This study aimed to investigate the in vitro effect of lavender essential oil and clotrimazole on isolated C. albicans from vaginal candidiasis. Materials and Methods . In this clinical trial, C. albicans isolated from the vaginal discharge samples was obtained. Results . The pairwise comparison showed that lavender and clotrimazole had a significant difference; this difference in the lavender group was lower than clotrimazole. But, after 48 hours, there was no difference seen between groups. There was a significant difference between clotrimazole and DMSO groups. Comparing the changes between groups based on the same dilution, at 24 h and 48 h in clotrimazole group, showed a significant difference two times in the fungal cell count that its average during 48 h was less than 24 h. A significant difference was observed between the two periods in lavender group, only at the dilutions of 1/20 and 1/80. The average fungal cell count after 48 h was also lower in lavender group. Conclusions . Given that the lavender has antifungal activity, this can be used as an antifungal agent. However, more clinical studies are necessary to validate its use in candida infection.